Human induced pluripotent stem cells for live cell cycle monitoring and endogenous gene activation - Kim, Rosa; Nagel, Sebastian H.; Liaw, Norman Y.; Zimmermann, Wolfram-H.; Zelarayán, Laura C.; Schoger, Eric (Stem cell research, 2024)
The fluorescence ubiquitination cell cycle inhibitor (FUCCI) has been introduced to monitor cell cycle activity in living cells, including human induced pluripotent stem cells (hiPSC) and derived cell types. We have recently developed hiPSC with stable expression of dCas9VPR for endogenous gene activation and a Citrine-tagged ACTN2 cell line to monitor sarcomere development and function in muscle cells. Here, we present dual and triple transgenic hiPSC lines developed by genomic integration of FUCCI with and without dCas9VPR into the ROSA26 and AAVS1 loci, respectively, in the previously introduced ACTN2-Citrine line. Functionality of the transgenes was demonstrated in the novel hiPSC line, which we introduce as Myo-CCER and CraCCER.
Online verfügbar: 5. August 2024, Artikelversion: 10. August 2024
Gesehen am 20.11.2024